Electrical properties of a composite of Polyurethane and ferroelectric ceramics - Sakamoto, W. K. [UNESP]; Kagesawa, S. [UNESP]; Kanda, D. H. [UNESP]; Das-Gupta, D. K. (Springer Nature, 1998)
Ferroelectric ceramic particles based on lead titanate zirconate (PZT) were dispersed in a polymer matrix based on castor oil. After the poling process, the pyroelectric activity of this composite was measured using a direct method in which a linear heating rate was applied to the pre-poled samples. The pyroelectric coefficient at 343 K is comparable with that of a PZT-poly(vinylidene fluoride) (PVDF) composite and significantly higher than that of PVDF. © 1998 Kluwer Academic Publishers.
Keywords: Ceramic materials; Ferroelectric materials; Lead compounds; Particles (particulate matter); Polarization; Polyurethanes; Pyroelectricity; Ferroelectric ceramics; Polymer matrix composites; Pyroelectric coefficient; Reinforced plastics